ACCELERATION OF LEARNING MANAGEMENT SYSTEM APPLICATION DEVELOPMENT IN THE EDUCATION SECTOR USING THE LOW CODE CONCEPT ON MICROGEN - Ega Wachid Radiegtya; Daniel Hasiholan Tinambunan; Rido Dwi Kurniawan; Richardus Eko Indrajit (Jurnal Teknik Informatika (Jutif), 2023)
The background of this research is to speed up application development which tends to take a long time. To respond this, researchers apply the concept of "Low-Code" referring to a software development approach by speeding up the manufacturing process by reducing the amount of code that needs to be written manually to be automated using the microgen platform. This research was tested on a case study of the development of a Learning Management System, making it faster and more efficient. System development used in this study is System Development Life Cycle (SDLC) method, which is a software development process model that is carried out in stages according to the existing mechanism. The backend created for this Learning Management System, uses the Microgen generator backend platform to automate the creation of the GraphQL API, and the database which is then consumed by the frontend which is the interface for the Learning Management System. This research resulted in a better understanding of how using automation tools like Microgen able to speed up the learning management system web development process. The research model with development (R&D) applied in this study uses a systematic model that requires each process to be fulfilled sequentially starting from the first stage to the final stage to produce a product and determine feasibility through product validation being developed. By adopting this automation approach, the previously time-consuming time required to generate the backend can be significantly reduced. Thus, the result is greater efficiency in Web Learning Management System development, savings in human resources, and better opportunities to respond to changing market or user needs.